Diabetes Professionals Must Seize the Opportunity in Mobile Health. (1st November 2013) - Brandell, Brian; Ford, Christopher
The number of diabetes management mobile applications (apps) available on the market has grown exponentially since 2009; however, most patients lack the skills necessary for finding relevant health care information. Thus, clinical best practices emphasize the need for ongoing patient education. Despite the importance of education in clinical guidelines, very few of these apps include education in their top functionalities. Most diabetes management mobile apps are not medical devices by definition, according to the U.S. Food and Drug Administration, and therefore do not require clearance or approval for market, and very few have been subject to clinical evaluation. There has been little research on the use of diabetes management mobile apps, marginalizing the role of diabetes professionals and educators in a burgeoning market, hungry for information and an improved quality of life. Still, mobile technology holds great promise as a platform for self-management. Health care providers must not only educate patients about these resources, but take steps to ensure that mobile apps follow accepted best practices and guidelines.